A Chaotic Sequence Watermarking Algorithm for Infrared Image - Xu Xiaoqing; Wang Jingzhong; Li Dan (2010 2nd International Conference on Information Engineering and Computer Science, 2010)
A watermarking algorithm for the infrared image copyright protection was developed. The whole process was based on integer wavelet transform. Encrypt the grey scale image watermark by Logistic chaotic sequence, and then decompose based on integer wavelet. Select the perceptually significant wavelet coefficients, and then inosculate in the given position of the original image. The watermark was detected hierarchically to save detection time. Experimental results show that the algorithm can be ensuring the range of temperature in ±1%, which did not affect the application of the infrared image. Meanwhile, it is implemented fast, invisible and robust enough.